THE EFFECT OF MACROECONOMIC VARIABLE ON RETURN AND VOLATILITY ON JII AND LQ-45 - Hizkisevia Ayu Cahyapuspita; Robiyanto Robiyanto (Universitas Sahid, 2021)
The study analyze the effect of macroeconomic variables on returns and volatility. Previous research examines the effect of macroeconomic variables on volatility is still limited, and it is interesting to study. Previous research focuses on the effect of macroeconomic variables on JCI; therefore, this study will use JII and LQ-45. The analytical technique used in this study is GARCH. This study states that the Dow Jones and Gold indexes significantly negatively affect JII and LQ-45 returns, while crude oil and exchange rates significantly positively affect JII and LQ-45. The Dow Jones variable has no significant positive effect on JII volatility and negatively affects LQ-45 volatility. The exchange rate has a significant negative effect on the volatility of JII and LQ-45. Crude oil prices have an insignificant negative effect on JII and LQ-45 volatility, and gold has a significant positive effect on JII and LQ-45 volatility.